43 Under utilisation of thrombolysis in the national ACS programme: the ST James experience. (28th September 2016) - Cuddy, S; Mellotte, G; Sullivan, V; Yearoo, I; Maree, A; Crean, P; Murphy, R
Abstract : Optimal reperfusion in STEMI is the key goal of the National ACS programme. The aims of the programme are a diagnosis to door time (DDT) of <90 minutes and a reperfusion time (RT) of <120 minutes, with a goal of Primary PCI (PPCI) as the method of reperfusion in 80% of STEMIs. Thrombolysis is an important reperfusion strategy where primary PCI cannot be offered to STEMI patients within recommended timelines. The aim of this study was to examine the number of patients outside the recommended time goals being referred to St James from other hospitals and hence to estimate the potential patient cohort that should be considered for thrombolysis prior to transfer to the Primary PCI centre. We used the Code STEMI database collected prospectively and HIPE data to identify our patient cohort. From January to December 2015 487 patients in total were identified as diagnosed with a STEMI or transferred to St James as part of the National ACS programme. Looking at all-comers; 222 (45%) were transferred from another hospital, 206 (42%) from the field, 29 (6%) from our ED. The average DDT of the patients from outside hospitals was 141 minutes (median 110, range 18–798), 63% were outside the 90 minutes DDT. The average RT was 148 minutes (median 128, range 25–599), 57% of the patients were outside the recommended 120 minutes for RT. Only 7 patients (1.4%) were thrombolysed prior to transfer. There are inevitable delays when arranging transfer of Code STEMI patients from an outside hospital to the primary PCI centre. It is expected that a proportion of patients will have to undergo thrombolysis as the initial reperfusion strategy. The data we collected in the largest PPCI centre in the country highlights that thrombolysis is being under-utilised and needs to be considered in all inter-hospital STEMI transfers.